Mechanical properties of sol–gel prepared nanocomposite coatings in the presence of titania and alumina-derived nanoparticles. (2nd January 2017) - Ershad-Langroudi, A.; Abdollahi, H.; Rahimi, A.
ABSTRACT: Hybrid nanocomposite coatings were prepared by sol–gel method using silica, titania and alumina nanoparticles derived from their alkoxides precursors; in the presence of 3-glycidoxypropyl-trimethoxysilane (GPTMS) and bisphenol A (BPA) on 1050 aluminium alloy substrate. The effect of type and ratio of nanoparticles on mechanical behaviour of the coatings were investigated by dynamic mechanical thermal analysis (DMA) and nanoindentation experiments. DMA results demonstrated that the values of the glass transition temperature ( T g ) and the temperature at maximum tan (δ), ( T t ) as well as the storage modulus of the hybrid samples depend mainly on the silane content and titania to alumina molar ratio of nanoparticles in the coating composition. In addition, nanoindentaion experiments were performed to study the mechanical properties such as hardness, elastic modulus and E / H ratio for the nanocomposite hybrid coatings. Nanoindentation results indicate that the homogenous reinforced structure was formed in the surface of nanocomposite coating with incorporation of titania and alumina-derived nanoparticles. The incorporation of TiO2 in comparison with AlOOH nanoparticles in the GPTMS-based coatings showed an improving effect on E / H ratio.